Mobile Payment Products in Indonesia: Is it a Lifestyle or a Need? - Setiobudi, Auditia; Sudyasjayanti, Christina; Singgih, Kevin Julianto; Gadi, Aiman Fauzi (Jurnal Manajemen Bisnis, 2021)
Research aims: This study aims to explore consumers’ preferences and perceptions of the use of mobile payments in Indonesia.Design/Methodology/Approach: This study used a comparison of Cronbach's Alpha and Cronbach’s Alpha if Item Deleted to find items preferred by mobile payment users. Factor analysis was employed to get consumers' perceptions of using mobile payment.Research findings: The results of this study found that consumer preferences for the use of mobile payments were compatible with their needs, helped complete work/needs, were used by the social environment, were easy to use, and made consumers happy. Meanwhile, consumers’ perceptions of mobile payment were formed from three factors: perceived ease of use, intention to use mobile payment, and mobile payment self-efficacy.Theoretical Contribution/Originality: This study examines the use of mobile payments in Indonesia further.Practitioners/Policy Implications: Mobile payments are not only a lifestyle because the products’ benefits are increasingly numerous and varied.Research Limitations/Implications: This research was only conducted in Java.